ANALISIS PENGARUH PENERAPAN DESIGN THINKING PADA BISNIS RINTISAN (STUDI KASUS: WIRAUSAHA MERDEKA UNIVERSITAS PADJADJARAN) - Delia Yunita Widiyanti; Rani Sukmadewi (POLITEKNIK LP3I JAKARTA, 2024)
A startup business is a business that is still in the development phase. Currently, the growth of startups in Indonesia is increasing rapidly, making Indonesia the 6th country with the most startups. The development of startups is certainly inseparable from the increasingly complex challenges in the business sector. This certainly makes design thinking relevant as a tool to understand users, identify problems and opportunities and create solutions. Quantitative research was conducted on students participating in the Merdeka Entrepreneur program at Padjadjaran University to find out whether the application of design thinking can have an influence on the startup business being run. The results of statistical analysis show that the design thinking variable has a positive value on startup businesses. With these findings, researchers highlight the importance of design thinking skills in bridging entrepreneurs in facing challenges in the business sector. Key words: Design Thinking, Startup